On the hypothesis of the equation for technical system state - D. J. Lobach (Вестник Дагестанского государственного технического университета: Технические науки, 2025)
Objective. The objective of the study is to formulate and demonstrate potential additional expert capabilities and a hypothesis to improve the quality of technical system projects by combining the analysis of technical characteristics of the project and human factor influence parameters. Method. The paper considers obtaining invariant relationships for some characteristics of technical systems, on the basis of which a hypothesis of the equation of state of a technical system is formulated. Result. Auxiliary analytical approaches have been developed to compare individual operational parameters of projects, conduct an expert assessment of technical systems of projects, devices and technologies. The use of the hypothesis of the equation of state of a technical system allows for expert assessments of the safety of a technical system. Conclusion. The use of additional expert approaches and hypotheses allows for the accumulation of experience in expert assessments, correlation analysis of data, determination of potential capabilities in the context of further modifications and upgrades of technical systems of the project, development of improved operational forecasts and strategies, and adoption of adequate management decisions.